PENINGKATAN KESADARAN LINGKUNGAN MELALUI SOSIALISASI PEMILAHAN SAMPAH PADA SISWA SDN 1 PADAK GUAR - Mohamad Prasetyo; Ghazali, Mursal; Imam, Muhammad Saparul; Putri, Lila; Ariyanto, Dimas Fatih; Mardatillah, Firda; Adhevina, Ihda; Hardianti, Alfita; Fitriani, Fitriani; Silva Utami, Rika; Araruna, Isroqul Ihsan (Jurnal Wicara, 2025)
Environmental awareness is an essential aspect of preserving nature from an early age. This study aims to enhance students' environmental awareness through waste sorting socialization at SDN 1 Padak Guar. The method used is a qualitative approach involving observation, interviews, and evaluation of students' behavioral changes before and after the socialization. The socialization activities include education on waste types, hands-on waste sorting practice, and the provision of supporting facilities. The results indicate an increase in students' understanding and awareness of the importance of proper waste sorting. This socialization has proven effective in instilling positive habits in waste management within the school environment. Therefore, this approach can serve as an environmental education model for other schools in maintaining cleanliness and environmental sustainability